Model Pembelajaran Children Learning In Science Dalam Meningkatkan Kemampuan Berpikir Kritis dan Sikap Ilmiah Siswa Sekolah Dasar - Virmayanti, Ni Komang; Suastra, I Wayan; Suma, I Ketut (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2023)
CLIS is a learning model that seeks to develop students' ideas or ideas about a particular problem in learning and construct ideas or ideas based on the results of observations or experiments. The steps in the CLIS model consist of five stages: orientation, elicitation of beliefs, restructuring of ideas, application of concepts, consolidation of ideas or review of change in views. The idea rearrangement stage is still divided into three parts: disclosure and exchange of ideas or clarification and discussion, opening a conflict situation or exposure to a conflict situation, and construction of new ideas and evaluation or building of new ideas and evaluation. The CLIS learning model is suitable for learning, especially in science subjects, which can develop students' critical thinking skills and scientific attitudes. Critical thinking ability is a high-level thinking ability. Critical thinking is strengthening cognitive skills or strategies in achieving goals. Critical thinking aims to consider what will be obtained in making decisions with critical and logical reasons. A scientific attitude is part of science learning. Scientific perspectives tend to be attitudes towards whether students like or dislike science learning.